2023
DOI: 10.1021/acsomega.3c04373
|View full text |Cite
|
Sign up to set email alerts
|

Revolutionizing Nanotechnology with Filago desertorum Extracts: Biogenic Synthesis of Silver Nanoparticles Exhibiting Potent Antioxidant and Antibacterial Activities

Abida Abida,
Mikhlid H. Almutairi,
Nadia Mushtaq
et al.

Abstract: In this study, we described the environmentally friendly biosynthesis of silver nanoparticles (AgNPs) utilizing ethanolic extract of Filago desertorum ( F. desertorum ) as a capping and reducing agent. We also looked at the antioxidant and antibacterial capacities of AgNPs. In order to determine the size, shape, and crystallinity of the created AgNPs, the current project was designed to produce AgNPs utilizing the crude extract of the F. desertorum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The IC 50 value of AgNPs was 23.22 ± 1.25 μg ml −1 , higher than that of vitamin C (18.57 ± 0.15 μg ml −1 ) control group. It has been reported that the IC 50 values of Filago desertum-AgNPs [36] and Cyphostemma auriculatum-AgNPs [37] were determined to be 144.61 and 55.66 μg ml −1 [36]. The obtained results imply that organic compounds, especially oleanolic acid, contributed to the antioxidant activity.…”
Section: Antioxidant Potential Of Agnpsmentioning
confidence: 69%
“…The IC 50 value of AgNPs was 23.22 ± 1.25 μg ml −1 , higher than that of vitamin C (18.57 ± 0.15 μg ml −1 ) control group. It has been reported that the IC 50 values of Filago desertum-AgNPs [36] and Cyphostemma auriculatum-AgNPs [37] were determined to be 144.61 and 55.66 μg ml −1 [36]. The obtained results imply that organic compounds, especially oleanolic acid, contributed to the antioxidant activity.…”
Section: Antioxidant Potential Of Agnpsmentioning
confidence: 69%
“…Due to their unique properties and applications, nanoparticles have recently gained attention [2,3]. At present, many nanoparticle manufacturing processes exist, including physical methods (plasma, chemical vapor deposition, microwave irradiation, and pulsed laser), biological methods (plants, bacteria, fungi, and alga), chemical methods (chemical reduction), and hybrid methods mixing two of these methods [4][5][6].…”
Section: Introductionmentioning
confidence: 99%